La SNEP : une entreprise publique de l’imprimerie (1944-1992) - Baptiste Giron (Cahiers d’histoire.)
Since the 19th century, the place of the press in French society has been at the origin of many debates, in particular on its relationship to money. The ordinances of 1944 supposedly attempted to overcome this problem. SNEP was the product of this attempt. This industrial establishment arose from the desire to break with the largely collaborationist, "old" pre-war press, to allow the underground newspapers of the Resistance to take over in a completely redesigned setting. This innovative company was founded on a democratic project which aimed to build an independent press, breaking with market logic. However, the abandonment of the change in the status of the press led this company to become a government tool during the cold war and colonial conflicts, before being liquidated in 1992 under the weight of economic globalization and new liberal policies.